Palm Olein as Renewable Raw Materials for Industrial and Pharmaceutical Products Applications: Chemical Characterization and Physicochemical Properties Studies - Darfizzi Derawi; Bashar Mudhaffar Abdullah; Hasniza Zaman Huri; Rahimi M. Yusop; Jumat Salimon; Nany Hairunisa; Nadia Salih (Advances in Materials Science and Engineering)
Palm olein (POo) is widely produced as edible oil in tropical countries. POo is considered as renewable raw material for the new industrial and pharmaceutical products synthesis based on its characterization. Palm olein was good on its viscosity index, oxidative stability, and flash and fire point. POo contained unsaturated triacylglycerols (TAGs): POO (33.3%); POP (29.6%) which plays an important role in chemical modification process to produce new industrial products. The double bond was detected on 1H-NMR (5.3 ppm) and 13C-NMR (130 ppm) spectra. The chemical compositions of POo were tested by using high performance liquid chromatography (HPLC) and gas chromatography (GC) techniques. This unsaturated oil is potentially to be used as renewable raw materials in chemical modification process to synthesise polyols, polyurethane, and biolubricant for industrial and pharmaceutical products application.